Assessment Programme Outcomes (POs) of the solid mechanics course for an engineering diploma programme / Fariz Aswan Ahmad Zakwan, Ruqayyah Ismail and Mohd. Zaini Endut - Ahmad Zakwan, Fariz Aswan; Ismail, Ruqayyah; Endut, Mohd. Zaini (Universiti Teknologi MARA, Pulau Pinang, 2022)
Most diploma programmes in Malaysia are accredited by the Engineering Accreditation Council (EAC) to ensure the quality of engineers produced by the country. POs for each programme is designed to pertain the abilities, knowledge, analytical capacity, attitude, and behaviour that students need to obtain through the course of the programme. This study focuses on the POs achievements of Solid Mechanics (ECS226), a fundamental engineering course for the Diploma in Civil Engineering (CEEC110), Centre for Civil Engineering Studies, Universiti Teknologi MARA (UiTM), Cawangan Pulau Pinang, Permatang Pauh Campus. The POs achievements were evaluated between two different academic sessions of 20202 (March - July 2020) and 20212 (March - August 2021). Based on the results, the outcome of the POs achievements between the two different sessions shows that the students' POs achievements varied on selected POs attached to this course. Through three different assessments (Quiz, Assignment and Final Assessment) which measure the PO1 and PO2 for this course, analytical trends can be identified for two different semesters. Key outcomes from this study revealed that PO1 had a relatively increasing trend while PO2 detected decreasing trends when two consecutive semesters were compared respectively. These trends were attributed from the continuous quality improvement (CQI) effectiveness of the previous semester, which led to the POs achievements in the following academic session.